(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Learning strategies are systematic steps that students use to achieve specific learning objectives. Use of effective learning strategies enables the students to efficiently manage large amount of information pertaining to preclinical subjects in medical schooland ensures better academic outcome. This study aims to explore the relationship between learning strategy and academic scores of preclinical medical students in Bangladesh. Materials and methods: This was a cross sectional study conducted during the period from January to December 2024. Data were collected from 192 1 st and 2 year students of two medical colleges through a questionnaire. The 50 items of the questionnaire were divided in nine subscales. SPSS was used for analysis.Unpaired t-test and ANOVA were used to compare means. Pearson’s correlation coefficients were calculated between each subscale score and academic performance. Results: Female students, students who study for longer hours and those living in hostel displayed significantly higher scores. In terms of correlation, critical thinking showed moderate but significant correlation (r=0.42, p=0.00) while metacognitive self regulation (r=0.22, p=0.03) time and study management (r=0.31, p=0.00) revealed small though significant correlations with the academic score. Conclusion: The results of the study will enable the educators to guide the students on efficient learning practices to ensure better academic outcome. JCMCTA 2025 ; 36 (2) : 59-64